Entering Negotiations: Early-Career Perspectives on the UN Conference of Parties and the Unfolding Climate Crisis - Ferrer, Erica M.; Cavole, Leticia M.; Clausnitzer, Simona; Dias, Daniela F.; Osborne, Tashiana C.; Sugla, Rishi; Harrison, Emma (Frontiers in Marine Science, 2021)
As the pressure to address the climate crisis builds, scientists must walk the line between research and activism. This was apparent at the 2019 United Nations (UN) Framework Convention on Climate Change – Conference of the Parties (UNFCCC – COP), the largest annual meeting to address the climate crisis via supranational policymaking. COP has convened annually since 1995 in effort to establish international agreements for the reduction of greenhouse gas emissions, and in 2015, was the launch pad for the UN Paris Climate Agreement (PCA). Here, we present our collective perspective as early-career researchers on COP, an institution that we believe plays a critical role in the future of our oceans. Given the current pledges from signatories to the PCA, Earth is expected to warm ∼3°C by 2100, with the majority of anthropogenic heat content stored throughout the ocean. For this reason, among others, we feel it is crucial for ocean scientists to have a baseline understanding of the negotiations unfolding at COP and within the UNFCCC. We also provide evidence that certain features/structures of COP formalize colonial hierarchies, marginalize certain groups, and threaten to perpetuate the drivers of the environmental crises we all face. Thus, we urge that the future of such gatherings include purposeful and self-reflective acts of restructuring the space they occupy, the solutions they advocate, and the ways in which power is distributed amongst participants. We balance our critique with examples of how this has already been successful at COP, particularly with respect to organizing around ocean-climate issues.